Mobile Game Adoption Model: Integrating Technology Acceptance Model and Game Features - Wahyu Rafdinal; Agri Qisthi; Sharnuke Asrilsyak (Faculty of Economics, Universitas Sriwijaya, 2020)
This study aims to analyze the factors in mobile game adoption that are influenced by game features and technology acceptance models.Partial least square is used to analyze the relationship between game features, perceived ease of use, perceived usefulness, attitude, and intention to play mobile games. This study uses a sample of 408 respondents who have played mobile games in the past month. The results showed that game features are a determinant of intention to play mobile games. Game features also affect players' intentions and attitudes to play mobile games if the game features are easy to play and useful when played. Increasing mobile adoption requires features that are easy to play and useful if played. It will affect the player's attitude and intention to play. Game developers, game designers and game companies must create game features that create a pleasant experience for players.This study bridges the gap in the literature on mobile game adoption by explaining the relationship between game features and technology adoption.